THE APPROACHES OF ACADEMIC MANAGEMENT AT SIRIWATWITTAYA SCHOOL BASED ON THE CONCEPT OF ENHANCING STUDENTS’ SELF – ESTEEM - Intaraamorn, Thaworn; Usaho, Chayapim (Academic Journal Phranakhon Rajabhat University, 2019)
The purposes of this research were: 1) to study the current state and desirable state of academic management and enhancing students’ self – esteem, and 2) to present the approaches for developing academic management to enhance students’ self – esteem. The population was the member of Siriwatwittaya School. There were 24 informants included the administrators and teachers. The research instruments were questionnaires (rating scale) and suitability and possibility of evaluation forms (rating scale). The data were analyzed by frequency distribution, percentage, mean, standard deviation, PNI modified, and mode. The results were as follows: the current and desirable state of academic management based on the concept of enhancing students’ self - esteem were in the high level ( = 4.167) and the highest level ( = 4.916). The first priority needs index was the instruction (PNI = 0.184); the second priority needs index was the instruction. (PNI = 0.182); and the last priority needs index was the assessment (PNI = 0.168). There were 3 approaches of academic management. The approaches sort by priority needs index were the curriculum development approach, the instruction approach, and the assessment approach.